(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to determine the nutritionals characteristics of athletes of the city of João Person who compete in national level. A sample of 66 athletes was constituted, being 50 men and 16 women, from the swimming modalities (11), athletism (15) karate (16), beach volleyball (09) and soccer (15). They had been submitted to an interview, had completed a recordatory of 24h and an inquiry of alimentary frequency. The data had been treated through descriptive statistics and by means of the qui-square, with level of significance adopted of 5%. Average values of caloric expense had been observed from 3048 Kcal (± 683,8) to 3206 Kcal (± 682,2), for the simplified and factorial forms respectively, with statistical significant difference between these two methods (p=0.020). The caloric ingestion was of 3860 Kcal (DP= 1396.1). Although the diet had a hipercaloric average, 31.8% of the citizens presented hypocaloric diet. The macronutrients were distributed like this: 58.5% of glicidies (± 9,0), 17.7% of protidies (± 4,4), and 23.8% of lipidies (±7,7). Social-economic level (p=0,325), educational formation (p=0,485) and an orientation by the nutritionist (0,367) had not been correlated with the nutritional quality. This paper concluded that the athletes present great variability in its alimentary profiles, which are not affected by social - cultural factors. The collected data pointed towards the necessity of the athlete accompaniment for a continuous and systematic presence of the nutritionist in training environments.